Is movement variability important for sports biomechanists? - Bartlett, R.; Wheat, J.; Robin, M. (Sports Biomechanics, 2007)
This paper overviews the importance for sports biomechanics of movement variability, which has been studied for some time by cognitive and ecological motor skills specialists but, until quite recently, had somewhat been overlooked by sports biomechanists. The paper considers biomechanics research reporting inter- and intra-individual movement variability in javelin and discus throwing, basketball shooting, and locomotion. The overview does not claim to be comprehensive and we exclude such issues as the theoretical background to movement and coordination variability and their measurement. We overview evidence, both theoretical and empirical, of inter-individual movement variability in seeking to achieve the same task goal, in contrast to the concept of "optimal" movement patterns. Furthermore, even elite athletes cannot reproduce identical movement patterns after many years of training, contradicting the ideas of motor invariance and "representative" trials. We contend that movement variability, far from being solely due to neuromuscular system or measurement "noise" - as sports biomechanists may have previously supposed - is, or could be, functional. Such functionality could allow environmental adaptations, reduce injury risk, and facilitate changes in coordination patterns. We conclude by recommending that sports biomechanists should focus more of their research on movement variability and on important related topics, such as control and coordination of movement, and implications for practice and skill learning.